Varstvo jedi in kuharskih receptov s pravicami intelektualne lastnine - Šuštar, Medeja (Pravni letopis, 2020)
The aim of this article is to determine whether culinary creations can be protected with intellectual property rights and to define the conditions under which such protection is possible. For the purposes of this article, culinary creations are divided into three following categories: the recipe, trade dress, and the taste of food. The recipe itself does not represent an individual creation, therefore, it cannot be protected by copyright. However, the recipe can be patented, whereas the trade dress can be protected by multiple rights, such as copyright, trademark, and model. Trademark only provides protection for the trade dress which serves as a means to distinguish similar products. The taste of food cannot be protected with intellectual property rights, as it does not meet the basic precondition for protection, i.e. that the object of protection is objectively identifiable. Taste, on the other hand, is indirectly protected by guaranteed traditional specialty. In my opinion, this is controversial since the protection of subjectively definable creations contradicts fundamental constitutional principle of legal security.
Keywords: avtorsko pravo; intelektualna lastnina; kulinarika